A Novel Greeting Selection System for a Culture-Adaptive Humanoid Robot. (10th April 2015) - Trovato, Gabriele; Zecca, Massimiliano; Do, Martin; Terlemez, Ömer; Kuramochi, Masuko; Waibel, Alexander; Asfour, Tamim; Takanishi, Atsuo
Robots, especially humanoids, are expected to perform human-like actions and adapt to our ways of communication in order to facilitate their acceptance in human society. Among humans, rules of communication change depending on background culture: greetings are a part of communication in which cultural differences are strong. Robots should adapt to these specific differences in order to communicate effectively, being able to select the appropriate manner of greeting for different cultures depending on the social context. In this paper, we present the modelling of social factors that influence greeting choice, and the resulting novel culture-dependent greeting gesture and words selection system. An experiment with German participants was run using the humanoid robot ARMAR-IIIb. Thanks to this system, the robot, after interacting with Germans, can perform greeting gestures appropriate to German culture in addition to a repertoire of greetings appropriate to Japanese culture.